SOCIAL-GEOGRAPHIC WORKS BY ACADEMICIAN ARKADIY ZHUKOVSKYY IN ENGLISH VERSION OF ENCYCLOPEDIA OF UKRAINE (VOL. I-V, 1984-1993) - Руденко, Валерій; Пирогівська, Алла (Human Geography Journal, 2016)
Social-geographic contribution of Academician Zhukovskyy (1922-2014) is disclosed in English version of Encyclopedia of Ukraine where his 237 works are presented. The author’s studies in political geography, geopolitics, historic geography, history of geography, social-geographic country study, geography of religions and social geography of Ukraine are analyzed. Ukrainian centralism, role and place of Ukrainians in all spheres of social life of their country and the world are distinctive features of scientist’s every publication.